Patient Safety Awareness Among Medical and Pharmacy Students at Admission: A Comparative Study - Miura K; Kohara S; Hase S; Sasamori C; Shu A; Kasai K; Yokoshima A; Fujishiro N; Otaki Y (Advances in Medical Education and Practice)
Kentaro Miura,1 Suguru Kohara,1 Shuho Hase,2 Chie Sasamori,3 Akihito Shu,4 Kenji Kasai,5 Asuka Yokoshima,1 Naofumi Fujishiro,6 Yasuhiro Otaki6 1Department of Medicine, Teikyo University, Tokyo, Japan; 2Department of Pharmaceutical Sciences, Teikyo University, Tokyo, Japan; 3Department of Obstetrics and Gynecology, St Luke’s International Hospital, Tokyo, Japan; 4Department of Neurosurgery, Kanto Medical Center NTT EC, Tokyo, Japan; 5Department of Rehabilitation Medicine, Kameda Medical Center, Chiba, Japan; 6General Medical Education and Research Center, Teikyo University, Tokyo, JapanCorrespondence: Kentaro Miura, Department of Medicine, Teikyo University School of Medicine, 1-11-2 Kaga, Itabashi Ward 173-8605, Tokyo, Japan, Tel +81-3-3964-1211, Fax +81-3-3964-8413, Email kenta.miura@jcom.zaq.ne.jpPurpose: Providing medical and pharmacy schools students with effective patient safety education is one of the important factors in improving the quality of health care delivery. To provide effective education, understanding the level of patient safety awareness among medical and pharmacy school students at the time of admission and implementing tailored educational approaches based on their characteristics are essential. This study was performed to measure and compare the level of patient safety awareness between medical and pharmacy school students at the time of admission, to aid in improving effectiveness of patient safety education.Methods: A total of 132 first-year medical school students and 367 first-year pharmacy school students enrolled at Teikyo University in 2019 completed an anonymous and self-administered questionnaire upon admission. The questionnaire included questions regarding the demographics of the participants as well as a translated and modified survey classifying patient safety awareness into “perception”, “knowledge”, and “attitude” which were evaluated on a 5-point Likert scale (Cronbach’s alpha coefficient was 0.70). To assess overall patient safety awareness, we calculated the total scores for the three sub-constructs using a 5-point Likert scale—Strongly Agree (5 points), Agree (4 points), Neutral (3 points), Disagree (2 points), and Strongly Disagree (1 point)—and compared these scores between the two groups.Results: The total scores (mean ± standard deviation) were 104.2 ± 10.2 for medical school students and 97.2 ± 9.9 for pharmacy school students (mean difference: 7.1, p < 0.001, 95% Confidence Interval (CI): 4.9– 9.2). After controlling for confounders through analysis of covariance, a statistically significant difference was observed between the two groups (Least Square mean: 5.6, p < 0.001, 95% CI: 3.3– 7.9). A higher percentage of medical school students exhibited positive responses across three sub-constructs when compared to their counterparts.Conclusion: Medical school students had a higher level of patient safety awareness than pharmacy school students at the time of admission, prior to receiving patient safety education.Keywords: patient safety education, medical student, pharmacy student, first-year student, medical school admission